The Inflammatory and Oxidative Status of Newly Diagnosed Class III and Class IV Lupus Nephritis, with Six-Month Follow-Up - José Ignacio Cerrillos-Gutiérrez; Miguel Medina-Pérez; Jorge Andrade-Sierra; Alejandra De Alba-Razo; Fermín Paul Pacheco-Moisés; Ernesto Germán Cardona-Muñoz; Wendy Campos-Pérez; Erika Martínez-López; Daniela Itzel Sánchez-Lozano; Andrés García-Sánchez; Tannia Isabel Campos-Bayardo; Alejandra Guillermina Miranda-Díaz (MDPI AG, 2023)
Lupus nephritis (LN) is the most frequent and severe complication of systemic lupus erythematosus (SLE). A prospective cohort with a six-month follow-up was performed. Twelve SLE patients diagnosed with LN Class III, twelve NL Class IV patients, and twelve healthy control subjects (HC) were included. SLE data, renal function, oxidants, antioxidants, and inflammation were determined at baseline and six-month follow-up. During the six-month follow-up, the SLE Disease Activity Index (SLEDAI-2K) decreased in both LN Class III (20.08 ± 6.92 vs. 11.92 ± 5.87, p < 0.001) and LN Class IV (25.33 ± 6.01 vs. 13.83 ± 5.52, p < 0.001) patients. Furthermore, the values of the C4 component also increased during follow-up for LN Class III (25.36 ± 6.34 vs. 30.91 ± 9.22, p = 0.027) and LN Class IV (12.18 ± 3.90 vs. 20.33 ± 8.95, p = 0.008) groups. Regarding inflammation markers, both groups presented decreased C-reactive protein (CRP), but this was only significant for patients with LN class III (7.93 ± 1.77 vs. 4.72 ± 3.23, p = 0.006). Renal function remained stable in both groups, with no changes in eGFR. Patients with LN Class III and Class IV showed higher baseline levels for lipoperoxides (Class III p < 0.01, Class IV p < 0.1) and carbonyl groups in proteins (Class III p < 0.01, Class IV p < 0.1) compared to HC. Moreover, both groups presented lower baseline values of total antioxidant capacity (Class III p < 0.01, Class IV p < 0.1) and catalase (Class III p < 0.01, Class IV p < 0.1) compared to HCs. However, antioxidant and oxidant markers did not show significant differences between baseline values and at six months for either of the two study groups. In conclusion, patients show an imbalance in the oxidative state characterized by the increase in the oxidants LPO and protein carbonyl groups and the decrease in the activity of the antioxidant enzymes TAC and CAT compared to HC. However, the patients did not present an increase in disease activity and renal function improvement. The glomerular filtration rate did not change during the length of the study, and SLEDAI -2K, C3, and C4 improved. The early co-management between Rheumatologists and Nephrologists is essential to prevent the rapid progression of LN. It would be interesting to administer antioxidant supplements to patients with a recent diagnosis of LN and evaluate its effect in a follow-up study.